2016
DOI: 10.1016/j.atherosclerosis.2016.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in the circle of Willis: Spatial differences in composition and in distribution of plaques

Abstract: Advanced atherosclerotic plaques in the CoW are relatively scarce and mainly located in the 4 large arteries, and mostly characterized by an early and stable phenotype, a low calcific burden, and a low frequency of IPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…In our subgroup analyses, the proximal vessel segments showed the largest incremental increase in the detection of abnormal segments. As intracranial atherosclerosis has a predilection for proximal intracranial arteries, our results suggest that abnormal but prestenotic lesions may not be detected accurately, which may underestimate disease prevalence.…”
Section: Discussionmentioning
confidence: 81%
“…In our subgroup analyses, the proximal vessel segments showed the largest incremental increase in the detection of abnormal segments. As intracranial atherosclerosis has a predilection for proximal intracranial arteries, our results suggest that abnormal but prestenotic lesions may not be detected accurately, which may underestimate disease prevalence.…”
Section: Discussionmentioning
confidence: 81%
“…The more advanced atherosclerotic changes were infrequently detected in intracranial artery until the very old years [ 16 , 51 ], such as calcified lesion first detected in the 6th decade, and ulcerated lesion first observed in the 9th decade [ 8 ]. A study of 1,220 segments of circle of Willis from 67 randomly chosen autopsy cases showed that early plaques were predominant (66%) and advanced plaques exceptional (15%), whereas complicated plaques were present in only 1% of lesions [ 52 ]. Figure 3 shows the plaque components on histology.…”
Section: Histopathological Evidence From Human Cadaversmentioning
confidence: 99%
“…In carotid artery involved with atherosclerosis, intraplaque hemorrhage was observed in as high as 19% to 97% within symptomatic lesions and 7% to 91% within asymptomatic lesions [ 53 , 54 ]. By contrast, a much lower prevalence of intraplaque hemorrhage was reported in studies involving intracranial arteries: only one lesion with intraplaque hemorrhage was reported in 205 intracranial arterial segments [ 55 ] and 6 of 1,220 segments had intraplaque hemorrhage among patients who had cardiovascular-related events [ 52 ]. But the samples of these two studies were taken at specific locations per circle of Willis specimen, which may lead to an underestimate of the prevalence of intraplaque hemorrhage.…”
Section: Histopathological Evidence From Human Cadaversmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of calcifications in the arteries in our sample is higher than reported in other cohorts with systemic analysis of the circle of Willis (5.4% versus 3% of all arteries assessed). 19 This discrepancy may relate to the difference in vascular risk factors and slightly higher proportion of men in our study. Additionally, we did not decalcified our specimen before fixation and embedding, which may have facilitate identification of calcium deposits in our sample.…”
Section: Discussionmentioning
confidence: 58%